The ten thousand doors of January - Harrow, Alix E. (Orbit, 2019)
In a sprawling mansion filled with peculiar treasures, January Scaller is a curiosity herself. As the ward of the wealthy Mr. Locke, she feels little different from the artifacts that decorate the halls: carefully maintained, largely ignored, and utterly out of place. Then she finds a strange book. A book that carries the scent of other worlds, and tells a tale of secret doors, of love, adventure and danger. Each page turn reveals impossible truths about the world and January discovers a story increasingly entwined with her own.